Traditions of Skepticism and Discourse of Post-Truth in British Post-Postmodern Novels - Drozdovskyi, Dmytro (Pitannâ lìteraturoznavstva, 2019)
In the paper, the forms of critical perception of reality inherent to the protagonists of contemporary British novels (“The Curious Incident of the Dog in the Night-Time”, “Carry Me Down”, “Little Stranger”, etc.) have been discussed. The author has analyzed strategies for reactivation of skepticism in British post-postmodern novel “Cloud Atlas” by D. Mitchell. The specificity of the representation of skepticism in literary post-postmodernism is investigated; in particular, theoretical considerations of L. Miroshnychenko, O. Boynitska and other experts in English/British literature have been developed. The peculiarities of dystopia as a part of the metageneric phenomenon of post-postmodernistic novel “Cloud Atlas” have been revealed. The features of representation of propositional and existential truths in contemporary British novel are outlined. The mechanisms of counteraction to the forms of post-truth and the simulacrum “truths” represented in “Cloud Atlas” as part of capitalist ideological discourse, which leads to a distorted perception of reality and civilization catastrophe, have been outlined. It is revealed that in “Cloud Atlas” there is a critique of hypertrophied consumerism and the loss by contemporary literature the ability to be the source of existential meanings. The specific features in human representation as a dual phenomenon in post-postmodern British novel (Nietzsche's conception of the revaluation of values and the will to power in “Cloud Atlas” is depicted ambivalently) has been explored in the paper. I state that post-postmodernism is a cultural paradigm that unites aesthetic and philosophy of modernism and postmodernism. Besides, the post-postmodern novel has a specific feature resulted in a special narrative mode that combines scientific discoveries that influence the narrative with a special philosophical realm. In the paper, David Mitchell’s novel “Cloud Atlas” has been discussed as an example of post-postmodern writing that reveals emotional sincerity and skepticism, utopic way of thinking and anticolonial discourse. The novel exploits epic beginning to involve the reader in a special atmosphere created by the omnipotent narrator. The end of the story is a metaphorical return to the beginning; however, the starting point was changed. The novel exploits six separate stories that are interlinked according to the idea of eternal returning presented by Nietzsche and realized in the novel in the image of “Cloud Atlas” (symphony). The reality in the novel is exploited as a multifaceted phenomenon and time is depicted according to super-string astrophysical theory. The research gives a clue to understanding the philosophical boarders of post-postmodernism and demonstrates the combination of different discourses (humanitarian and scientific) in contemporary British novel. The paper provides new findings in explaining philosophical parameters of post-postmodern novels.